Medium Analysis Of Satire Stand Up Comedy Shows In Kompas Tv: Episode Of Ernest Prakasa-My Beloved Wife - Tarigan, Veronika Ita Karina; Kinasih, Putri Rindu; Budipratiwi, Rizki Ayu; Citrayomie, Ayoedia Gita (Petanda: Jurnal Ilmu Komunikasi dan Humaniora, 2024)
All human beings definitely want to be happy. In recent years, jokes have developed in various events, one of which is Stand Up Comedy, which is now increasingly successful in On Air activities at a number of television stations. In this journal, researcher is search data by interviewing the Executive Producer of StandUp Comedy Kompas TV, comedy scriptwriters and making a number of observations. That way researchers get results and know the communication strategy of StandUp Comedy community in maintaining its existence. This study aims to find out what are the contents of messages contained in the text of the comic material, with a qualitative approach using the Ferdinand De Saussure method of semiotic analysis. The formulation of problem is to examine message contained in the StandUp Comedy material and its effect on many people if it is broadcast, especially television media. Stand Up Comedy performances are not just entertainment. It can be a tool for social criticism for a person, a group of people, and a certain community. The more showtimes of new comedians, the more they will train each sense of humour so that they are able to make a show with mature material.